An investigation of trends in precious metal and copper content of RAM modules in WEEE: Implications for long term recycling potential. (February 2017) - Charles, Rhys Gareth; Douglas, Peter; Hallin, Ingrid Liv; Matthews, Ian; Liversage, Gareth
Highlights: Au, Ag, Pd and Cu content of historic PC RAM modules were investigated. Temporal reductions in Pd content and increases in Cu content have been identified. Projections of recycling potential of future WEEE items accounting for these trends have been made. The importance of temporal compositional variations in recycling potential projections is considered. Factors affecting future WEEE recycling viability and future outlook are considered. Abstract: Precious metal (PM) and copper content of dynamic-RAM modules placed on the market during 1991–2008 has been analysed by AAS following comminution and acid digestion. Linear regression analysis of compositional data ordered according to sample chronology was used to identify historic temporal trends in module composition resulting from changes in manufacturing practices, and to project future trends for use in more accurate assessment of future recycling potential. DRAM was found to be 'high grade' waste with: stable levels of gold and silver over time; 80% reduction in palladium content during 1991–2008; and 0.23 g/module/year increase in copper content with a 75% projected increase from 2008 by 2020. The accuracy of future recycling potential projections for WEEE using current methods based on static compositional data from current devices is questionable due to likely changes in future device composition. The impact on recycling potential projections of waste laptops, smart phones, cell phones and tablets arising in Europe in 2020 resulting from a 75% increase in copper content is considered against existing projections using static compositional data. The results highlight that failing to consider temporal variations in PM content may result in significant discrepancies between projections and future recycling potential.